Rethinking the Paleogene Tectonostratigraphy and Petroleum Systems of Indonesia: Moving Beyond Simplistic Basin Models - Ian Longley (Berita Sedimentologi, 2026)
A pervasive paradigm in Southeast Asian geosciences posits a uniform, synchronous tripartite sequence for Paleogene basin evolution: regional rifting, thermal sag, and middle-to-late Miocene structural inversion. However, critical evaluation of hard chronostratigraphic and structural data reveals this rigid model is overly simplistic and frequently inaccurate. Instead, the Paleogene basins of Indonesia exhibit highly localized, diachronous, and episodic tectonic events that cannot be explained by regional generalizations like the rigid "Tapponnier Extrusion Model." This paper deconstructs these generalized assumptions by analysing three distinct tectonostratigraphic settings: non-marine syn-rifts (e.g., Central and South Sumatra) characterized by episodic extension and poor palynological age control; marine syn-rifts (e.g., East Java) where early marine incursions provide high-confidence biostratigraphic dating and robust seals; and mixed syn-rift/sag non-marine sections (e.g., West Natuna and Malay Basins) where a massive post-rift lacustrine sag sequence hosts the primary petroleum systems. Regional data demonstrates that tectonic initiation was highly diachronous, spanning from the Middle Eocene to the Miocene, while structural records preserve multiple, independent compressional phases dating back to the Early Oligocene. Ultimately, true chronostratigraphic control remains weak across non-marine Paleogene intervals in Western Indonesia due to a reliance on long-range data. To reduce exploration risk and accurately assess petroleum systems, geoscientists must abandon generic, synchronized structural templates. Instead, exploration strategies must adopt rigorous, data-driven frameworks supported by localized mapping of distinct rifts, sags, and multi-phase structural inversions.